Effect of glissade-step on kinetic and kinematic variables of stag ring leaps with and without throw-catch of the ball in rhythmic gymnastics - Akkari-Ghazouani, H.; Mkaouer, B.; Amara, S.; Jemni, M.; Chtara, M. (Sports Biomechanics, 2023)
This study focuses on certain characteristics of the jump take-offs in rhythmic gymnastics (RG). Rhythmic gymnasts always perform their jumps with the same preferred run-up technique, proceeded by a chassé-step in most of the cases. The overall idea was to analyse other step-techniques that could be performged on one-leg, which could prepare jumps. The aim of this study was to compare kinetic and kinematic variables between three-stag ring leaps with and without throwing-ball, performed using the glissade-step as a preparatory phase for take-off with one-leg these were as follows: glissade stag ring leap without-ball (GSWB), throw-ball glissade stag ring leap (TBGS) and glissade throw-ball stag ring leap (GTBS). Seven members of the Tunisian RG national team took part in this study. The technical elements were recorded in 2D using two-cameras on a specially designed floor carpet where a force-plate was integrated. The results showed that the three-leaps had significant impacts on the performance variables, especially on the force, the velocity and the flexibility. The GTBS was the most effective leap as the throw took place during the jump, which has increased its technicality and the applied physical variables, the vertical force, the rate of force development, the horizontal and vertical velocities and displacements.